Analisis Efisiensi Rantai Pasok Menggunakan Metode SCOR (Supply Chain Operations Reference) di CV Kopi Biji Palembang - Aisyah, Nyimas Siti; Hardini, Septa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the supply chain efficiency of CV Kopi Biji Palembang using the Supply Chain Operations Reference (SCOR) model. The research is motivated by the challenges faced by local coffee companies in managing inventory, distribution, and resource utilization effectively. This is a quantitative descriptive study, with data collected through field observation, Likert-scale questionnaires, interviews, and literature review. The analysis focuses on the five core SCOR processes: Plan, Source, Make, Deliver, and Return, supported by the Analytical Hierarchy Process (AHP) to determine performance weighting. The findings indicate that the main weaknesses lie in distribution and inventory management, while production planning is relatively efficient. Recommendations include optimizing distribution flow, implementing data-driven inventory control, and strengthening supplier collaboration to enhance overall supply chain efficiency.